2014
DOI: 10.1590/1414-431x20143695
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between deep venous thrombosis and inflammatory cytokines in postoperative patients with malignant abdominal tumors

Abstract: Deep venous thrombosis (DVT) is a common surgical complication in cancer patients and evidence that inflammation plays a role in the occurrence of DVT is increasing. We studied a population of cancer patients with abdominal malignancies with the aim of investigating whether the levels of circulating inflammatory cytokines were associated with postoperative DVT, and to determine the levels in DVT diagnoses. The serum levels of C-reactive protein (CRP), interleukins (IL)-6 and IL-10, nuclear transcription factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 23 publications
0
33
0
1
Order By: Relevance
“…Inflammatory states and higher levels of pro-inflammatory cytokines are known risk factors for DVT [23]. Furthermore conditions that increase bacterial translocation such as IBD have been implicated in the development of venous thrombosis through higher circulating levels of lipopolysaccharide (LPS) along with increased expression of Toll-like receptor 4 (TLR-4), an innate immune receptor responsible for LPS recognition [20].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory states and higher levels of pro-inflammatory cytokines are known risk factors for DVT [23]. Furthermore conditions that increase bacterial translocation such as IBD have been implicated in the development of venous thrombosis through higher circulating levels of lipopolysaccharide (LPS) along with increased expression of Toll-like receptor 4 (TLR-4), an innate immune receptor responsible for LPS recognition [20].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have demonstrated that levels of inflammatory cytokines and chemokines are increased in the peripheral blood of patients with DVT. Du and Tan (10) identified that certain inflammatory factors including IL-6, CRP and NF-κB are closely associated with DVT. Krieger et al (30) suggested that changes in CRP levels and the erythrocyte sedimentation coefficient may induce acute lower extremity DVT.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is a type of invasive examination and increases the risk of complications occurring, including thrombus detachment, allergic reactions and increased thrombosis severity, which limits its application in the clinic (8). Recent studies have demonstrated that biomarkers including C-reactive protein (CRP), D-dimer and interleukin (IL)-6, exhibit beneficial clinical value in the early diagnosis of DVT; however, these biomarkers are still not a substitute for lower extremity venous imaging (9)(10)(11). At present, the mechanism of DVT is unclear, which greatly limits screening for DVT diagnostic markers.…”
Section: Introductionmentioning
confidence: 99%
“…[8] One of the studies revealed the increasing of IL-10 level in patients with venous thrombosis in comparison with the control group. [9] In addition, Konenkov et al (2016) and Shal'nev (2007) consider that IL-10 suppresses the tissue factor expression, therefore, inducing hypocoagulation and increasing plasminogen activator secretion. [10,11] According to other authors, decreasing of IL-10 serum level is associated with poor prognosis in patients with MI.…”
Section: Research Articlementioning
confidence: 99%